2021
DOI: 10.1002/joc.7403
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclones over the Arabian Sea during the monsoon onset phase

Abstract: Generally, monsoon conditions are unfavourable for cyclogenesis in the Arabian Sea due to the strong vertical wind shear present over the basin which prevents the vertical development of cyclones. However, there are instances where tropical cyclones form over the basin during the onset phase of the Indian summer monsoon (ISM). The current study examines the evolution of the synoptic conditions in the years during 1979–2019 in which a cyclone forms during the onset phase of the ISM. The effect of various atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…If the forecasts indicate a convectively suppressed MJO over the Arabian Sea during the monsoon onset period, the likelihood of MOV formation during that period could potentially be low. The findings from another recent study by Dhavale et al (2022), may potentially help in the predictability of cyclones from the MOV. Dhavale et al (2022) studied the evolution of large-scale synoptic conditions over the Indian subcontinent and adjoining regions preceding the formation of Arabian Sea cyclones during the monsoon onset phase.…”
Section: Discussionmentioning
confidence: 85%
“…If the forecasts indicate a convectively suppressed MJO over the Arabian Sea during the monsoon onset period, the likelihood of MOV formation during that period could potentially be low. The findings from another recent study by Dhavale et al (2022), may potentially help in the predictability of cyclones from the MOV. Dhavale et al (2022) studied the evolution of large-scale synoptic conditions over the Indian subcontinent and adjoining regions preceding the formation of Arabian Sea cyclones during the monsoon onset phase.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, the convection during monsoon season is characterized by bigger droplets and a steep vertical reflectivity profile with maximum frequency occurrence. It is clearly shown that the season has a significant influence on the precipitation characteristics of the TCs formed over the Arabian Sea (Dhavale et al., 2022). Further, some analysis is required for determining the variation in the precipitation characteristics of the TCs happening in the initial, mature, and dissipating stages, which has not been addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Dhavale et al. (2022) concluded that the synoptic condition in the Arabian Sea favors cyclogenesis mainly during the weak monsoon onset phase, aligning with the warm sea surface temperature. Observed variation in favorable conditions and large‐scale parameters in different seasons substantially influences the nature of TCs in terms of intensity and rainfall distribution (Kranthi et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Its unidirectional winds and associated strong vertical wind shear prohibit cyclone formation. Although occasional cyclogenesis is possible during a weak monsoon onset phase with weak circulation (Dhavale et al ., 2021), the pre‐monsoon and post‐monsoon months generally offer the most favourable conditions, with variable winds, little vertical wind shear, positive vorticity and warm sea‐surface temperatures (SSTs) (Chowdhury et al ., 2020).…”
Section: Arabian Sea Cyclones: Seasonality and Distributionmentioning
confidence: 99%